Análise do comportamento de prismas de alvenaria de tijolos de solo-cimento-RCC - Zanatta, Katia Cristina (2015)
The search for new technologies, combined with the concept of conscious sustainable development, allows the growth of actions aimed at recycling waste. This study investigated the use of construction waste - RCC in the manufacture of soil-cement hollow brick. Three cement contents were studied: 6%, 8% and 10%, combined with different doses of RCC: 20%, 40% and 60% by mass. The soil was sandy in mixtures. The RCC used consisted of remains of ceramic, concrete and mortar. Four dosages were selected for the manufacture of bricks, however, due to molding issues for the evaluation of the prisms was no need for a new dosing with 50% soil, 50% of RCC and 10% cement. 350 bricks were made with this dosage, seeking enforcement of prisms to evaluate the behavior of masonry produced with these components for resistance to compression and the modulus of elasticity. The results demonstrated the feasibility of use of the material studied for the proposed purpose.